Pemikiran Badiuzzaman Said Nursi terhadap kenabian: ibrah kisah-kisah nabi yang terdapat dalam Rasail an-Nur - Mohd Noor, Muaz; Suyurno, S. Salahudin; Mohd Zaini, Norazri; Shahruddin, Mohd Solahuddin; Norman, Mohd Paidi (Universiti Teknologi MARA, Kelantan, 2018)
This study is an attempt to elaborate on metaphysical thinking of a mujaddid, a highly influential intellectual and reformer of the 20th century, Sheikh Badiuzzaman Said Bin Mirza (Said Nursi) on the question of prophethood. This study gives emphasis on several key concepts associated with the prophetic nature, such as the concept of divinity, miracles, and importance messages of the prophet. This study focuses on the great books of Said Nursi, Rasāil an-Nūr, which is sourced from the al-Qurān and al-Hadith. For further interpretation of each debate, the author has presented an overview of some ‘scholars’ of various schools of thought as a comparison. From the aspect implementation of the study, the authors have adopted the use of documentation to gather all the necessary data, while the method of inductive, deductive and comparative is used to analyze all the data collected. The findings of this study show that, there have several prophets mentioned directly by the Said Nursi, such as the prophet Adam a.s, prophet Yusuf a.s, prophet Yunus a.s, prophet Ayub a.s, prophet Khidir a.s, and Prophet Muhammad s.a.w. Of course, these prophets have their own advantage and privilages from Said Nursi’s view until they are highlighted in writing, and preaching. Then, Said Nursi appears to have proved that the prophetic style of thinking can solve the issue of the community that exist on this day, though the prophecy has passed over 1400 years ago.